Potential damage surfaces and their control in abandoned mine caverns for compressed hydrogen energy storage - Rui LIU; Shuwei ZHOU; Shikang QIN; Xiuhan HE; Jianye FENG; Xiaodong ZHENG (Meitan kexue jishu)
Retrofitting abandoned mine shafts and using them for compressed hydrogen energy storage is an effective way to reuse waste resources and to realize the “double carbon” strategy. Due to mining action, abandoned mine shafts are usually in a non-isobaric state, and the non-isobaric state reduces the reliability of energy storage in the chambers. Based on the shear energy release characteristics during the fracture process, a phase-field fracture model considering the evolution of gas pressure, temperature and shear energy release was developed and validated; secondly, based on the proposed phase-field model, the initiation and development of potential fracture surfaces of chambers with different widths of coal pillars and level differences were investigated; and lastly, the proposed phase-field fracture model was combined with actual projects to investigate the effect of different treatment methods on the potential fracture surfaces of chambers. Finally, the proposed phase-field fracture model was combined with the actual project to investigate the effect of the treatment and fracture triggers under different surrounding rock treatment methods. The results show that the proposed phase-field fracture model can better characterize the fracture initiation location, fracture triggers and development process of the potential fracture surface of the chamber; the width of the coal pillar directly affects the fracture initiation pressure of the chamber; the wider the coal pillar, the higher the fracture initiation pressure of the chamber, and the overall fracture surface is mainly shear; the fracture surface of the chamber is divided into primary fracture surface and secondary fracture surface, and the wider the width of the pillar, the deeper the secondary fracture surface develops; the level difference between the chamber and the mining site also affects the fracture initiation pressure of the chamber; the fracture initiation pressure is also influenced by the level difference between the chamber and the mining site. The difference between the level of the chamber and the quarry also affects the fracture initiation pressure. As the height difference between the chamber and the quarry increases, the fracture initiation pressure of the perimeter rock increases and then decreases, and the fracture surfaces appear to be bifurcated due to tensile stresses; the fracture stopping study of the potential fracture surfaces shows that the most effective way to improve the hydrogen storage performance of the chamber is to add more anchors at the bottom of the chamber, followed by grouting to strengthen the perimeter rock and the weak effect of filling in the void areas. The cause of fracture in the chamber with the anchor ropes was shear stress, and the cause of fracture development along the anchors was tensile stress.